(3MOhO GdCMcGes - (3eUfac, Ydj Hf eMeO (B( (3eLO GdOjf (B) (3Hf eSYhO, J (B875 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO GdPj CfRd Ydj YHOg GdMOhO hGdCMcGe CeG HYO ajbhd Ydj Hf eLO GdOjf Hf eMehO Hf eSYhO GdTGg OhOj GdHSWGej deG TGgOJ Cgd GdReGf bGUQI Gdgee aj GdYdhe GdTQYjI aGdJeS ef dg bOe Cf CLeY GdMOhO GdTQYjIs
(3BNQgG (B:s
(3ade jcf Yf YjH MGOK hgPG eYfi bhd eMeO GdLfhf YjH dGRe CHOG GfJgi , Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 9s
(3eYLe GdeDdajf (B2 / 530s
(3cTa GdXfhf (B1 / 635s
(3TPQGJ GdPgH (B7 / 319s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs